2019
DOI: 10.1021/acs.nanolett.9b02568
|View full text |Cite
|
Sign up to set email alerts
|

Kinked Silicon Nanowires: Superstructures by Metal-Assisted Chemical Etching

Abstract: We report on metal-assisted chemical etching of Si for the synthesis of mechanicallystable, hybrid crystallographic orientation Si superstructures with high aspect ratio, above 200. This method sustains high etching rates and facilitates reproducible results. The protocol enables the control of the number, angle and location of the kinks via successive etch-quench sequences. We analysed relevant Au mask catalyst features to systematically assess their impact on a wide spectrum of etched morphologies that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…© 2020 Wiley-VCH GmbH More recently, Sandu et al reported another simple and efficient MacEtch method to fabricate high-aspect ratio and orientation-customized kinked SiNWs with hybrid crystallographic orientation. [112] This etching protocol relies on repetitive etchquench sequences to induce the kinks using low-surface tension ethanol, as shown in Figure 9d-f. These experiments further proved the versatility of MacEtch in fabricating complex silicon superstructures.…”
Section: (10 Of 21)mentioning
confidence: 99%
See 2 more Smart Citations
“…© 2020 Wiley-VCH GmbH More recently, Sandu et al reported another simple and efficient MacEtch method to fabricate high-aspect ratio and orientation-customized kinked SiNWs with hybrid crystallographic orientation. [112] This etching protocol relies on repetitive etchquench sequences to induce the kinks using low-surface tension ethanol, as shown in Figure 9d-f. These experiments further proved the versatility of MacEtch in fabricating complex silicon superstructures.…”
Section: (10 Of 21)mentioning
confidence: 99%
“…MacEtch of silicon refers to the wet etching of silicon in the presence of noble metal particles or films, which are physically or chemically deposited onto the silicon surface to enhance silicon etching at open‐circuit potential (OCP) in oxidizing hydrofluoric acid (HF) aqueous solutions. [ 35–157 ] Within the last couple of years, MacEtch of silicon in HF aqueous solutions has aroused great interest in the research community and is presently one of the most popular top‐down approached for micro/nanofabrication owing to its cost‐effectiveness, simplicity, versatility, and scalability. [ …”
Section: Origin Mechanism and Development Of Metal‐assisted Chemicamentioning
confidence: 99%
See 1 more Smart Citation
“…In general, two approaches have been adopted for the fabrication of different NWs: top-down or bottom-up (Akbari-Saatlu et al, 2020). In most of the research we have investigated, the bottom-up approach is preferred with the popular vaporliquid-solid chemical vapor deposition (VLS-CVD) used (Calaza et al, 2015); others are achieved using the top-down approach with an etching process, for example, metal-assisted wet chemical etching (MaCE) or reactive ion etching (RIE) (Wolfsteller et al, 2010;Sandu et al, 2019;Radamson et al, 2020). Some relevant measurements of the TE properties have also been developed during the study of NWs (Rojo et al, 2013;Borup et al, 2015;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the process works with a wide range of noble metals. The main focus in research has been set on the noble metals gold (Au) and silver (Ag) [ 2 , 17 19 ]. Other studies also investigated palladium (Pd), platinum (Pt), and to a lesser extent even copper (Cu) [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%